2014
DOI: 10.1039/c4cp04215h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain size and microstructure on radiation stability of CeO2: an extensive study

Abstract: To investigate the variation in the radiation stability of ceria with microstructure under the electronic excitation regime, ceria samples sintered under different conditions were irradiated with high energy 100 MeV Ag ions. The ceria nanopowders were synthesized and sintered at 800 °C (S800), 1000 °C (S1000) and 1300 °C (S1300), respectively. The samples with widely varying grain size, densities and microstructure were obtained. The pristine and irradiated samples were studied by X-ray diffraction (XRD), Scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 33 publications
6
39
1
Order By: Relevance
“…Some authors have attributed this peak to oxygen ions with unusual coordination in a defective CeO x (x<2) structure [34]. Recently, reports assigned this peak to oxygen vacancies in CeO 2 [35,36]. In this work, the presence of A c c e p t e d M a n u s c r i p t hydroxyl groups or carbonate is not found.…”
Section: Page 8 Of 22contrasting
confidence: 54%
“…Some authors have attributed this peak to oxygen ions with unusual coordination in a defective CeO x (x<2) structure [34]. Recently, reports assigned this peak to oxygen vacancies in CeO 2 [35,36]. In this work, the presence of A c c e p t e d M a n u s c r i p t hydroxyl groups or carbonate is not found.…”
Section: Page 8 Of 22contrasting
confidence: 54%
“…Such kind of anomalies has attributed to the prevalence of point defects such as oxide formation. 11,58 The average nanocrystal size of each catalyst was calculated from Ag(111) peak using Scherrer formula. 11 The sizes were estimated as 8.8, and 8.1, nm for AgNCs/rGO_AA, and AgNCs/rGO_NaBH 4 , respectively, which are in good agreement with the predetermined particle sizes by HRTEM.…”
Section: 55mentioning
confidence: 99%
“…The modes observed at 307 cm −1 can be assigned to the in‐plane vibration of the Ti–O bonds in an off centric Ti‐displaced TiO 6 octahedra as in the ferroelectric phases of BaTiO 3. Similarly, the mode observed at 252 cm −1 can be assigned to the rotation of the TiO 3 units of the TiO 6 octahedra. These two modes are the characteristic frequencies observed only in tetragonal BaTiO 3.…”
Section: Resultsmentioning
confidence: 91%
“…investigated radiation (940 MeV Au at fluence of 1.5×10 13 ions/cm 2 ) induced amorphization of CaZrO 3 . The ion‐induced amorphization as a function of fluence has been monitored by in situ X‐ray diffraction (XRD) studies and the increasing lattice strain has been attributed to the amorphization process . From many reports, we found that the radiation tolerance of the different oxide materials has been improved by increasing the density of grain boundaries or making them nanocrystalline and also depends on stoichiometry or nonstoichiometry and structure type of the materials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation